Corrosion degradation of ship hull steel plates accounting for local environmental conditions. (1st September 2018) - Zayed, A.; Garbatov, Y.; Guedes Soares, C.
Abstract: Corrosion degradation of ship plates is predicted at different ship locations based on limited information on the local environmental conditions. The ship spaces are classified according to their chemical and physical characteristics that affect the corrosion behaviour. The parameters of the calibrated models, expressing the corrosion degradation from both sides of ship plates, are used to derive other parameters for corrosion models expressing the corrosion degradation at each side of the corresponding plates. The derived models are then used to develop corrosion models for other ship spaces, where no real corrosion measurement data are available. Highlights: Corrosion degradation of ship plates is predicted at different ship locations based on local environmental conditions. The ship spaces are classified according to their chemical and physical characteristics that affect the corrosion behaviour. The models from corrosion on both sides of plates, are used to derive the parameters for corrosion at each side. The derived models are then used to develop corrosion models for other ship spaces.